Study of the Role of the Tumor Microenvironment in Ovarian Cancer (MICO): A Prospective Monocentric Trial - Martina Arcieri; Eleonora Capezzali; Stefano Restaino; Sara Pregnolato; Laura Mariuzzi; Alessandro Mangogna; Maria Orsaria; Angelica Tulisso; Silvia Tonon; Maria De Martino; Miriam Isola; Lorenza Driul; et al. (Cancer Reports)
ABSTRACT Background Ovarian cancer (OC) is one of the most aggressive tumors requiring new therapeutic approaches. Immunotherapy represents an opportunity, but to date, OC patients do not appear to benefit from current protocols. A better understanding of the composition of the tumor microenvironment (TME), especially in its immune components, could unveil mechanisms of immune suppression in a useful way to predict response to therapies and develop new therapeutic approaches. Method The MICO (tumor MICroenvironment of Ovarian cancer) study is a single‐center observational study. Starting from peritoneal biopsy of high‐grade serous ovarian carcinoma (HGSOC), the purpose of the MICO study is to generate tumor patient‐derived organoid (PDOs) cultures and evaluate the concordance between in vitro platinum‐based chemotherapy sensitivity and in vivo sensitivity. Simultaneously, we will characterize through multiparameter cytofluorimetric analysis the composition of the OC TME, focusing on B lymphocytes and mast cells whose roles in ovarian cancer remain controversial and underinvestigated. Furthermore, patients experiencing recurrence will be longitudinally followed to monitor changes in the TME composition and the responsiveness of PDOs to in vitro stimulation with drugs. Discussion The association between the composition of the TME, the reactivity of the PDOs, and patients' disease progression will be analyzed to identify whether specific subpopulations of tumor‐infiltrating immune cells could be predictive factors of the disease outcomes. The comparison of molecular profiles, in vitro response to drugs, and clinical‐pathological data will allow the definition of a pattern capable of predicting the response of the primary tumor for the identification of those patients who may benefit from specific treatment. Strengths and Limitations The results of our study could help to better understand the OC behavior, may have implications for the development of effective immunotherapy and targeted pharmacological therapies for epithelial OC in a personalized medicine perspective. This will be a monocentric trial with an involvement of only 43 patients, so further studies will need to confirm our results. Trial Registration The clinical trial has been registered at Clinical‐Trials.gov with the identifier NCT06272240 on 02/14/2024